Characterization of α-amylases obtained from Geobacillus strains isolated from binh chau hot spring - Thoa, Nguyễn Kim; Hoa, Trần Thị; Mấn, Trần Đình; Thuỷ, Tạ Thị Thu (Vietnam Journal of Biotechnology, 2018)
Binh Chau is famous for being a rare open-air hot spring with the highest mouth temperature in Vietnam. From water and sludge samples collected in Binh Chau hot spring, 64 aerobic thermophilic bacterial strains were isolated. Based on the identified characteristics of Bacillus genus, the optimum growth temperature as well as the ability to hydrolyze starch, 22 strains belonging to Geobacillus genus were selected for study on their α-amylase properties. Alpha-amylase from 11 of 22 strains showed pHopt ≥ 7. The optimum temperature of α–amylase ranged from 50oC to 90oC in different strains, of which seven strains showed the Topt of α–amylase at 90 oC. Thermostability of these strains at 90oC was identified, showing the half life of the three most prominent strains TĐ3.2, TG2.2, TG3.7 strains at 5.5 hours, 3.25 hours and 6.5 hours, respectively. Moreover, the addition of 5 mM Ca2+ resulted in improving α–amylase activity of 4 strains (TĐ3.2, TG2.2, TG3.1 and TG3.7) from 1,15 - 1,55 times, as well as in increasing thermostability of all enzymes produced by 7 strains with their new half life varied from 2-7 houts. Comparative analyses of sequences of 16S rRNA gene from the TĐ3.2, TG2.2, TG3.7 strains indicated that they were most closely related to G. caldoxilosilyticus, G. thermoglucosidasius, and G. stearothermophilus respectively (with the homology of 99%, 98% and 99%, respectively). Thus, it could be assumed that the genetic materials of microorganisms in Binh Chau hot spring are of great interest of exploitation in very near future.